The Auditory Cortex: A Synthesis of Human and Animal Research - Heil, Peter; Scheich, Henning; Budinger, Eike; Konig, Reinhard (Psychology Press, 2005)
Understanding human hearing is not only a scientific challenge but also a problem of growing social and political importance, given the steadily increasing numbers of people with hearing deficits or even deafness. This book is about the highest level of hearing in humans and other mammals. It brings together studies of both humans and animals thereby giving a more profound understanding of the concepts, approaches, techniques, and knowledge of the auditory cortex. All of the most up-to-date procedures of non-invasive imaging are employed in the research that is described. Contents: Preface. Part I: Auditory Cortical Fields and Their Functions. E. Budinger, Introduction: Auditory Cortical Fields and Their Functions. J.H. Kaas, T.A. Hackett, Subdivisions and Connections of the Auditory Cortex in Primates: A Working Model. P. Morosan, J. Rademacher, N. Palomero-Gallagher, K. Zilles, Anatomical Organization of the Human Auditory Cortex: Cytoarchitecture and Transmitter Receptors. D.A. Hall, Sensitivity to Spectral and Temporal Properties of Sound in Human Non-Primary Auditory Cortex. S. Clarke, M. Adriani, E. Tardif, "What" and "Where" in Human Audition: Evidence From Anatomical, Activation, and Lesion Studies. K. Imaizumi, C.C. Lee, J.F. Linden, J.A. Winer, C.E. Schreiner, The Anterior Field of Auditory Cortex: Neurophysiological and Neuroanatomical Organization. H.E. Heffner, The Neurobehavioral Study of Auditory Cortex. M. Brosch, H. Scheich, Non-Acoustic Influence on Neural Activity in Auditory Cortex. J.F. Brugge, I.O. Volkov, R.A. Reale, P.C. Garell, H. Kawasaki, H. Oya, Q. Li, M.A. Howard III, The Posterolateral Superior Temporal Auditory Field in Humans: Functional Organization and Connectivity. P. Belin, R.J. Zatorre, Voice Processing in Human Auditory Cortex. H. Ackermann, I. Hertrich, W. Lutzenberger, K. Mathiak, Cerebral Organization of Speech Sound Perception: Hemispheric Lateralization Effects at the Level of the Supratemporal Plane, the Inferior Dorsolateral Frontal Lobe and the Cerebellum. Part II: Coding of Sounds. M. Brosch, Introduction: Coding of Sounds. P. Heil, H. Neubauer, Toward a Unifying Basis of Auditory Thresholds. J.C. Middlebrooks, S. Furukawa, G.C. Stecker, B.J. Mickey, Distributed Representation of Sound-Source Location in the Auditory Cortex. B. Wible, T. Nicol, N. Kraus, Encoding of Complex Sounds in an Animal Model: Implications for Understanding Speech Perception in Humans. J.J. Eggermont, Correlated Neural Activity: Epiphenomenon or Part of the Neural Code? A.E.P. Villa, Spatio-Temporal Patterns of Spike Occurrences in Freely-Moving Rats Associated to Perception of Human Vowels. E. Ahissar, M. Ahissar, Processing of the Temporal Envelope of Speech. I. Taniguchi, S. Sugimoto, A. Hess, J. Horikawa, Y. Hosokawa, H. Scheich, Spatio-Temporal Patterns of Responses to Pure Tones and Frequency Modulated Sounds in the Guinea Pig Auditory Cortex. I. Nelken, L. Las, N. Ulanovsky, D. Farkas, Levels of Auditory Processing: The Subcortical Auditory System, Primary Auditory Cortex, and the Hard Problems of Auditory Perception. S.J. Eliades, X. Wang, Dynamics of Vocalization-Induced Sensory-Motor Interactions in the Primate Auditory Cortex. Part III: Plasticity, Learning, and Cognition. R. König, Introduction: Plasticity, Learning, and Cognition. J-M. Edeline, Learning-Induced Plasticity in the Thalamo-Cortical Auditory System: Should We Move From Rate Code to Temporal Code Descriptions? H. Scheich, F.W. Ohl, H. Schulze, A. Hess, A. Brechmann, What Is Reflected in Auditory Cortex Activity: Properties of Sound Stimuli or What the Brain Does With Them? D. Irvine, M. Brown, R. Martin, V. Park, Auditory Perceptual Learning and Cortical Plasticity. F.W. Ohl, H. Scheich, W.J. Freeman, Neurodynamics in Auditory Cortex During Category Learning. J. Fritz, M. Elhilali, S. Shamma, Task-Dependent Adaptive Plasticity of Receptive Fields in Primary Auditory Cortex of the Ferret. J. Rüsseler, W. Nager, J. Möbes, T.F. Münte, Cognitive Adaptations and Neuroplasticity: Lessons From Event-Related Brain Potentials. "The Auditory Cortex: A Synthesis of Human and Animal Research is a remarkable meeting of (no less than 70) experts concerned with how the brain processes sounds...provides novel ideas on the place of the auditory cortex in a bigger scheme of cortical and perceptual processing. A plethora of contemporary questions is present throughout the text...The Auditory Cortex may be most useful to graduate students and investigators with a fair awareness of issues in the field of auditory research, but it also is appropriate as an up-to-date reference text on the auditory cortex." —PsycCRITIQUES "...this book gives a really in-depth presentation, by worldwide experts in this domain, about what is known (and unknown) on the topic. Many important questions are addressed...many interesting issued are raised..." —Journal of Deaf Studies and Deaf Education